2023
DOI: 10.2340/jrm.v54.3199
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assessment of Spastic Muscles in Ambulatory Chronic Stroke Survivors Reveals Function-Dependent Changes

Abstract: Objective: To correlate ultrasound characteristics of spastic muscles with clinical and functional measurements in chronic stroke survivors.Methods: Ultrasound assessment and clinical and functional assessments were performed in 28 ambulatory stroke survivors (12 females, mean age 57.8 ± 11.8 years, 76 ± 45 months after stroke).Results: Muscle thickness in the affected side was decreased compared with the contralateral side (p < 0.001). The decrease was more evident in the upper limb muscles. On the affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…This study is part of a larger project in chronic stroke survivors with spastic hemiplegia recruited from the outpatient clinic of the Institute for Rehabilitation and Research (TIRR) Memorial Hermann in Houston, Texas 16,17 . Inclusion criteria were (1) chronic stroke (at least 6 mos after stroke onset) with hemiplegia, (2) stroke confirmed with brain imaging (computed tomography or magnetic resonance imaging), (3) presence of spasticity in the affected UL and/or LL, and (4) at least household ambulation with or without an assistive device.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of a larger project in chronic stroke survivors with spastic hemiplegia recruited from the outpatient clinic of the Institute for Rehabilitation and Research (TIRR) Memorial Hermann in Houston, Texas 16,17 . Inclusion criteria were (1) chronic stroke (at least 6 mos after stroke onset) with hemiplegia, (2) stroke confirmed with brain imaging (computed tomography or magnetic resonance imaging), (3) presence of spasticity in the affected UL and/or LL, and (4) at least household ambulation with or without an assistive device.…”
Section: Methodsmentioning
confidence: 99%
“…This study is part of a larger project in chronic stroke survivors with spastic hemiplegia recruited from the outpatient clinic of the Institute for Rehabilitation and Research (TIRR) Memorial Hermann in Houston, Texas. 16,17 Inclusion criteria were (1) chronic stroke (at least 6 mos after stroke onset) with hemiplegia, (2) stroke confirmed with brain imaging (computed tomography or magnetic resonance imaging), (3) presence of spasticity in the affected UL and/or LL, and (4) at least household ambulation with or without an assistive device. Exclusion criteria included inability to follow instructions, medical instability, pregnant women, a history of phenol injection within the last 2 yrs or a history of botulinum toxin injection in last 4 mos, a history of peripheral musculoskeletal disorders that affect grip strength or walking, or current use of intrathecal baclofen pumps.…”
Section: Subjectsmentioning
confidence: 99%
“…Ultrasound imaging has gained attention for its ability to non-invasively and affordably assess muscles' internal morphology without ionizing radiation [20]. Monjo et al [21] and Gonzalez-Buonomo et al [22] have utilized ultrasound imaging and observed reduced muscle thickness in the paretic lower extremity of poststroke individuals. Nevertheless, previous technical constraints restricted these technologies to evaluating muscle contraction patterns and internal morphological changes only in static conditions (i.e., recumbent [21,22] or sitting [21] position) among participants.…”
Section: Introductionmentioning
confidence: 99%